(untitled) (KYAMC Journal, 2023)
Renal primitive neuroectodermal tumor (renal PNET) or renal Ewing sarcoma (renal ES) is a rare, rapidly growing malignant small round cell tumor with poor prognosis. A 32-years-old Bangladeshi male patient presented with right loin pain, fever and anemia. On CT imaging a large (18x10.5x10.0 cm) renal mass was discovered. On suspicion of malignancy, a biopsy was taken from the mass. Microscopic evaluation showed features consistent with malignant small round blue cell tumor. Immunohistochemical stains showed diffuse and strong positive reaction to CD-99 and negative for WT-1, CD-3 and CD-20, which confirmed the diagnosis of renal PNET. After 6 cycles of combined chemotherapy, the patient was relatively well and at 6 months follow-up he showed no evidence of metastasis or recurrence. KYAMC Journal Vol. 13, No. 04, January 2023: 257-260